Africa's Pulse, February 2012 : An Analysis of Issues Shaping Africa's Economic Future - World Bank (Washington, DC, 2014)
This Africa's pulse newsletter includes the following headings: recent economic trends; global economic developments; and trends and outlook for Sub-Saharan Africa.